Влияние параметров зарядной цепи на ток в разрядном контуре магнитно-импульсной установки. Обработка экспериментальных исследований - Батыгин, Юрий Викторович; Гнатов, Андрей Викторович; Гнатова, Щасяна Валиковна; Сабокарь, Олег Сергеевич (НТУ "ХПИ", 2011)
Статья посвящена определению степени влияния параметров зарядной цепи на формирование импульса тока в разрядном контуре при разряде накопителей емкостной энергии. Проведена обработка экспериментальных данных, полученных с помощью индукционного датчика – пояса Роговского. Проанализировано влияние параметров зарядной цепи на форму и характеристики разрядного тока.

This article is devoted to determining of influence of charge circuit parameters upon the current pulse forming in the discharging circuit during discharge of a capacity energy storage bank. Processing the experimental data received with help the induction gage- belts Rogovsky are spent. Analysis of the influence on the discharged current form and its characteristics are resulted.
Influence of charge contour parametrs upon the discharge contour current in magnet-pulse installations. Processing of experimental reserches
Keywords: МИОМ; МИУ; импульс тока; накопитель емкостной энергии; пояс Роговского; charge contour; discharge contour; current form